Phytohormonal dynamics in the abscission zone of Korla fragrant pear during calyx abscission: a visual study - Zheng, Lingling; Wen, Yue; Lin, Yan; Tian, Jia; Shaobai, Junjie; Hao, Zhichao; Wang, Chunfeng; Sun, Tianyu; Wang, Lei; Chen, Chen (Frontiers in Plant Science, 2024)
Introduction Phytohormones play a crucial role in regulating the abscission of plant organs and tissues. Methods In this study, the ultrastructure of the sepals of Korla fragrant pears was observed using a transmission electron microscope, and high-performance liquid and gas chromatography were used to analyze the dynamic changes of phytohormones in the abscission zone during the calyx abscission process of Korla fragrant pears, and mass spectrometry imaging was applied to ascertain the spatial distribution of phytohormones. Results The results revealed that the mitochondria in the abscission zone of the decalyx fruits were regularly distributed around the cell wall, and the chloroplasts were moderately present. In contrast, in the persistent calyx fruit, the corresponding parts of the abscission zone showed a scattered distribution of mitochondria within the cells, and there was a higher number of chloroplasts, which also contained starch granules inside. Mass spectrometry imaging revealed that ABA was enriched in the abscission zone of the decalyx fruit, and their ionic signal intensities were significantly stronger than those of the persistent calyx fruit. However, the ionic signal intensities of Indole-3-acetic acid (IAA) and Gibberellin A3 (GA3) of the persistent calyx fruit were significantly stronger than those in the abscission zone of the decalyx fruit and were concentrated in the persistent calyx fruit. 1-Aminocyclopropanecarboxylic Acid (ACC) did not show distinct regional distribution in both the decalyx and persistent calyx fruits. Furthermore, before the formation of the abscission zone, the levels of IAA, GA3, and zeatin (ZT) in the abscission zone of the decalyx fruits were significantly lower than those in the persistent calyx fruits by 37.9%, 57.7%, and 33.0%, respectively, while the levels of abscisic acid (ABA) and ethylene (ETH) were significantly higher by 21.9% and 25.0%, respectively. During the formation of the abscission zone, the levels of IAA, GA3, and ZT in the abscission zone of the decalyx fruits were significantly lower than those in the persistent calyx fruits by 41.7%, 71.7%, and 24.6%, respectively, while the levels of ABA and ETH were significantly higher by 15.2% and 80.0%, respectively. After the formation of the abscission zone, the levels of IAA and GA3 in the abscission zone of the decalyx fruits were lower than those in the persistent calyx fruits by 20.8% and 47.8%, respectively, while the levels of ABA and ETH were higher by 271.8% and 26.9%, respectively. In summary, during the calyx abscission process of Korla fragrant pears, IAA and GA3 in the abscission zone inhibited abscission, while ABA and ETH promoted calyx abscission. These research findings enrich the understanding of the regulatory mechanism of plant hormones on calyx abscission and provide a theoretical basis for the study of exogenous plant growth regulators for regulating calyx abscission in Korla fragrant pear.